Gas Chromatography-Mass Spectrometry (GC-MS) Validated Microbial Inoculation: Saving Wild Agarwood Through Sustainable Biotechnological Cultivation - Sabella, Justin; Samuel, Lihan (2025)
This study develops an innovative fungal biotechnology to accelerate resin formation in Aquilaria species for sustainable agarwood production. Three microbial consortia, including F1 (Trichoderma sp. and Aspergillus sp.), F2 (Fusarium sp. and Penicillium sp.),and F3 (Trichoderma sp., Lasiodiplodia sp. and Curvularia sp.), were inoculated into Aquilaria species using a bottle drip method, an efficient and low-cost technique. Gas Chromatography-Mass Spectrometry (GC-MS) analysis revealed that F3 produced the superior resin yield, with exclusive aromatic compounds (e.g., guaia-1 (10),11-diene and cryptomeridiol) during the dry seasons. This biotechnological approach using optimised fungal consortia and inoculation methods can enhance agarwood production sustainably, reducing reliance on wild harvesting. This study method aligns with green technology and SDG 15 by promoting eco-friendly cultivation, minimising environmental impact, and meeting global demand without endangering natural populations. The success of F3 inoculants demonstrates the potential of fungal Biotechnology as a scalable solution for sustainable agarwood industries.